"Think before you type": the effectiveness of implementing an anti-cyberbullying project in an EFL classroom. (2nd January 2018) - Chen, Cheryl Wei-yu
ABSTRACT: Cyberbullying takes place when the Internet is used purposefully to cause harm or discomfort to a specific person or group of persons. Because of the fast growth of digital technologies, cyberbullying is replacing physical bullying and becoming a prevalent social problem around the world. This study outlines the author's efforts of integrating David Kolb's experiential learning theory, project-based learning, and a critical approach to language education to engage a group of Taiwanese college English-as-a-foreign-language students about the issues related to cyberbullying and the importance of healthy Internet behaviors. The results indicated that the 9-week project work heightened students' awareness of cyberbullying and other social issues and enhanced their language skills. Students also held an overall positive attitude toward the project work. To conclude the article, several research directions are suggested to continue this line of inquiry.